False memories in social anxiety disorder (Archives of Clinical Psychiatry, 2017)
Background False memories are memories of events that never occurred or that occurred, but not exactly as we recall. Events with emotional content are subject to false memories production similar to neutral events. However, individual differences, such as the level of maladjustment and emotional instability characteristics of Social Anxiety Disorder (SAD), may interfere in the production of false memories. Objectives This study aimed to assess the effect of emotion in memory performance for an event witnessed by participants with and without SAD. Methods Participants were 61 young adults with SAD and 76 without any symptoms of SAD who were randomly assigned to watch a story with or without emotional arousal. Participants answered a subjective scale of emotion about the story and a recognition memory test. Results Participants with SAD recovered more true memories and more false memories for the non-emotional version compared to the emotional version of the story. Overall, participants with SAD produced fewer false memories compared to those without SAD. Discussion This finding suggests that social anxiety may have a significant impact on emotional memory accuracy, which may assist in the development and improvement of techniques for therapeutic intervention.